Potensi Senyawa Kuersetin dalam Daun Jambu Biji (Psidium guajava L.) sebagai Pengobatan Demam Berdarah Dengue - Safitri, Nasywa Aulia; Marwa Zileikhadira Manzalina; Muhammad Farras Abiyyu F; Nasyada Fadhila Rahmadini; Mahacita Andanalusia (Lombok Medical Journal, 2023)
Abstract: Dengue is one of the most common mosquito-borne diseases in tropical and subtropical climates. So far there are no effective antivirals available for the treatment of DENV infection, which in this case requires alternative treatments that can be a cure as well as prevention for dengue fever. Alternative treatment that can be used is by using plants, one of which is guava. In guava leaves, there are various compounds that are efficacious as anti-dengue fever, namely flavonoid compounds such as quercetin and tannins which are believed to inhibit the growth of dengue viruses. The purpose of writing this manuscript is to discuss the potential of quercetin compounds in guava leaves in the management of dengue fever. Keywords: Dengue hemorrhagic fever, alternative medicine, antiviral, guava leaf, quercetin, ethnomedicine